The Effect of Digital Literacy, Soft Skills, and Self-Efficacy on The Work Readiness of Students in The Accounting Program at Private Vocational Schools in East Jakarta - Maria Tul Qibtiah; Ati Sumiati; Adam Zakaria (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine: (1) the effect of digital literacy on work readiness among students of private vocational high schools majoring in Accounting in East Jakarta, (2) the effect of soft skills on work readiness among students of private vocational high schools majoring in Accounting in East Jakarta, (3) the effect of self-efficacy on work readiness among students of private vocational high schools majoring in Accounting in East Jakarta, and (4) the simultaneous effect of digital literacy, soft skills, and self-efficacy on work readiness among students of private vocational high schools majoring in Accounting in East Jakarta. This research is a quantitative study using a survey method. The population consisted of 210 twelfth-grade Accounting students from As-Sa'adah Vocational High School Jakarta, BPS&K 1 Vocational High School Jakarta, and Nurul Islam Vocational High School Jakarta. A sample of 138 students was selected using proportional random sampling. Data were collected through a questionnaire and analyzed using multiple linear regression using SPSS version 31. The results indicate that (1) digital literacy has a positive and significant effect on work readiness, (2) soft skills have a positive and significant effect on work readiness, (3) self-efficacy has a positive and significant effect on work readiness, and (4) digital literacy, soft skills, and self-efficacy simultaneously have a positive and significant effect on students' work readiness.